Innovative solutions : what designers need to know for today's emerging markets - Chavan, Apala Lahiri; Prabhu, Girish V (Boca Raton, FL : CRC Press, 2011)
'Expanding into emerging markets brings with it a specific set of challenges for designing products and services. Not only do cultural differences play a role in what, how, and why customers behave the way they do, but existing technologies, distribution channels, and the wants and needs of consumers become additional challenges when establishing market shares in the developing world. Innovative Solutions: What Designers Need to Know for Today's Emerging Markets describes the landscape of these new markets and discusses research and design methodologies tailored to them''Local designers and researchers offer insight directly from the depths of India, China, and other parts of the world. They take an in-depth look at user research methods in underserved communities, new tools such as ecosystems mapping to define the elements impacting innovation and design decisions, and methodologies to develop solution spaces based on the output from user research studies. The book then presents real-life examples through case studies and interviews. The case studies draw not only from the authors' work with clients such as HP Labs, Nokia, Haier, Philips, Intel, and A Piece of Pie, but also from user experience and the results of innovation research across the globe. The interviews include conversations with leaders in innovation such as Roopa Purushothaman, Tapan Parikh, Ram Sehgal, Steve Portigal, Dmitry Volkov, and Darelle van Greunen''A fascinating perspective of the users and ecosystem in emerging nations, the book provides deeper insights on how a user-centered innovation and design approach has been applied in practical settings. Examining the challenges of innovating and designing for emerging markets, it incorporates research and practice to explore new ways of uncovering the riches and opportunities in innovation and design for emerging markets.'--BOOK JACKET
Case study 8: Philanthropy by design: Chulha: healthy, indoor cooking / Simona Rocchi, Unmesh Kulkarni -- Case study 9: Info Ladies: empowering remote rural areas with knowledge / Mosharrof Hossain, Forhad Uddin, Sarit Arora -- Case study 10: Cultural effects of status and relationships in usability testing / Dr. Alvin W. Yeo -- Interview 1: How did it all begin? A conversation with Roopa Purushothaman -- Interview 2: Advertising, culture and emerging markets: a conversation with Ram Sehgal -- Interview 3: Conversation with Tapan Parikh, a multicultural computer scientist who wanders the emerging markets -- Interview 4: What you see is what you get? Not so for the ethnographer, says Steven Portigal -- Interview 5: Dmitry Volkov on users, innovation, design and other things Russian -- Interview 6: Darelle Van Greunen on the difference that design and innovation can make to users in an emerging country
Includes bibliographical references and index
Keywords: New products; User-centered system design; Cross-cultural studies